Kriteria Pemimpin Menurut Pandangan Islam - Belia Fasra; Syahidin Syahidin (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Everyone is a leader and will be responsible for his leadership. In this discussion, the leader in question is someone who is liked and chosen by the community to hold the baton of power or leadership in a certain area. In this regard, the Qur'an has explained several criteria for determining leaders. Leadership is defined as a person's ability to influence and encourage others to act according to a common goal. To influence organizational goals, inspire followers to follow through on goals, and make recommendations to improve group culture is part of leadership. In an Islamic perspective, the role of leadership is very important in social interactions.